Efficacy of lipopolysaccharide antigen of Yersinia ruckeri in rainbow trout by intraperitoneal and bath immersion administration - Ispir, Unal; Dorucu, Mustafa (Elsevier Sci Ltd, 2014)
In this study, Intraperitoneal (IP) and bath immersion (BI) vaccine trials were conducted in fish with a mean weight of 6.3 g. Rainbow trout vaccinated with lipopolysaccharide (LPS) was 50 mg/L protein concentration and challenged by IP injection with 9.8 x 10(6) cell/ml of Yersinia ruckeri at 45 days post-immunization had a relative percent survival (RPS). To obtain an effective bath immersion vaccine against yersiniosis, LPS preparation was obtained from the Y ruckeri and with the LPS antigen. After 28 and 60 days vaccinated fish with first and second immunizations by LPS were challenged via intraperitoneal injection with 9.8 x 10(6) cell/ml of Y. ruckeri for evaluating the mortality rates and calculating the relative percentage of survival (RPS). RPS value of experimental groups, which was significantly (P < 0.05) larger than that of the control group. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Lipopolysaccharide; Yersinia ruckeri; Intraperitoneal vaccine; Bath immersion vaccine; Response; Rainbow trout